2016
DOI: 10.5195/ijms.2016.159
|View full text |Cite
|
Sign up to set email alerts
|

Association between Muscle Mass and Body Mass Index in Elderly Diabetic Patients Attending Tertiary Care Center in Bangalore, India

Abstract: Background: Sarcopenia is a disorder causing age-related loss of muscle mass. Its multifaceted nature has been linked to an increased risk of disability and mortality. Equally, obesity is a well-known risk factor for a host of disorders. A combination of sarcopenia and obesity in elderly diabetics can synergistically lead to increased insulin resistance and risk of metabolic syndrome. This study aimed to identify the association between sarcopenia and obesity in elderly diabetic patients by a cost-effective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Since arterial hypertension, dyslipidemia, chronic heart failure, atrial fibrillation, obesity, chronic kidney disease, and neoplastic disease are common comorbidities in T2DM patients that request medical therapy and appropriate management, physicians should make appeal to therapeutic solutions with a lower risk of drug-drug and food-drug interactions when available (e.g., non-vitamin K antagonists oral anticoagulants could be selected over vitamin K antagonists to prevent thromboembolic events in patients with atrial fibrillation, more research should be conducted to explore the potential uses of phytochemicals with clinical benefits, fewer drug-drug interactions and antioxidant properties, reconsideration of primary prevention strategies, etc.) [20,21,22,23,24,25,26]. In a similar study, Geitona et al reported that diabetic patients younger than 65 years were less likely to exhibit polypharmacy as compared to diabetic patients aged 66 or more ( p = 0.005).…”
Section: Discussionmentioning
confidence: 99%
“…Since arterial hypertension, dyslipidemia, chronic heart failure, atrial fibrillation, obesity, chronic kidney disease, and neoplastic disease are common comorbidities in T2DM patients that request medical therapy and appropriate management, physicians should make appeal to therapeutic solutions with a lower risk of drug-drug and food-drug interactions when available (e.g., non-vitamin K antagonists oral anticoagulants could be selected over vitamin K antagonists to prevent thromboembolic events in patients with atrial fibrillation, more research should be conducted to explore the potential uses of phytochemicals with clinical benefits, fewer drug-drug interactions and antioxidant properties, reconsideration of primary prevention strategies, etc.) [20,21,22,23,24,25,26]. In a similar study, Geitona et al reported that diabetic patients younger than 65 years were less likely to exhibit polypharmacy as compared to diabetic patients aged 66 or more ( p = 0.005).…”
Section: Discussionmentioning
confidence: 99%
“…In this context the South Asian community is ethnically and phenotypically different from Eastern and South Eastern Asia (which include countries like China, Hong Kong, Japan, Singapore, South Korea, Taiwan, and Thailand) [ 48 , 53 , 54 ]. These ethnic differences in body composition have clinical significance [ [55] , [56] , [57] ]. A known phenotype of South Asian obesity is the ‘thin-fat obesity’ or ‘sarcopenic obesity’, also known as normal weight obesity that has similar cardio-metabolic risk as obesity [ 37 , 38 , 58 , 59 ].…”
Section: Consensus Processmentioning
confidence: 99%
“…Literature from South Asia was scarce until 2014 [ 43 ]. However, new data and publications are slowly emerging from this region [ 6 , 11 , 33 , 34 , 36 , 52 , 57 , 73 ]. This has been helpful in understanding sarcopenia from South Asian perspective, and in formulating a consensus on screening, diagnosing, and managing sarcopenia in this patient population.…”
Section: Consensus Processmentioning
confidence: 99%
“…The prevalence of sarcopenia among T2DM patients has been observed to be 16.2% compared to only 2.4% in healthy controls [ 23 ]. The prevalence of pre-sarcopenia among Asian Indians with diabetes has been observed to be as high as 39.5% [ 28 ] while the incidence of sarcopenia has been observed to be 12.5% among males and 5.4% among females [ 29 ]. This is a worrisome trend given the immense burden of diabetes in India.…”
Section: Accelerated Sarcopenia In Chronic Diseasesmentioning
confidence: 99%